Optimalisasi Parenting Orang Tua Untuk Anak Disabilitas: Sebuah Studi Eksplorasi Siswa Difabel Di Probolinggo - Nining Winarsih; Siti Aminah (Journal of Contemporary Islamic Education, 2024)
This article discusses how the role of parents is extremely important in motivating children with disabilities in terms of communication and providing support to the child. It explores the role of teachers in assisting students with disabilities, including providing guidance and support in interacting with peers and offering motivation. The purpose of this study is to understand the role of parents in motivating their children in the educational sphere, focusing on emotional control, communication, and interaction within the school environment and the community. This research employs a qualitative method with a field study focus, using phenomenological research design and snowball sampling. It focuses on parents of students in Maron Wetan Village, Probolinggo District. Data collection techniques include in-depth interviews, observation, and documentation. Data analysis is conducted in four stages: data collection, data reduction, data presentation, and conclusion drawing. The study reveals findings about the lack of parental knowledge in parenting, resulting in children with disabilities feeling unmotivated to learn. It indicates that the issue in motivating these children lies in the parents' limited knowledge of parenting.